A Conceptual Framework for Understanding Parliamentary Skills and Competences: Bridging Public Policy and Legislative Studies - Muñoz-Del Campo, N (OXFORD UNIV PRESS, 2025)
The effective functioning of legislative bodies is essential to democratic systems. While the performance of Members of Parliament (MPs) has been widely studied, a significant gap remains regarding the skills and competences required to effectively fulfill their duties. This study addresses this gap by adapting the updated Policy Capacity Framework from policy studies-encompassing analytical, operational, political, deontological, and human capacities-to the parliamentary context. By integrating values like ethics, empathy, and social responsibility, the framework highlights the individual capacities that enhance institutional performance and democratic representation. Through a structured literature review and content analysis, this research develops the preliminary Parliamentary Capacity Framework (PACF) to assess and categorize the skills and knowledge essential for parliamentary functions. The PACF bridges the gap between what MPs are expected to do and their actual capabilities, offering insights to improve legislative performance and democratic outcomes. It also provides a foundation for designing capacity-building programs tailored to diverse parliamentary contexts. Finally, the PACF supports future research by offering a structured approach to studying parliamentary capacity, fostering interdisciplinary dialogue and innovation in assessing legislative work.